A model of morphogen transport in the presence of glypicans III. (October 2016) - Małogrosz, Marcin
Abstract: We analyse a stationary problem for the two dimensional model of morphogen transport introduced by Hufnagel et al. The model consists of one linear elliptic PDE posed on ( − 1, 1 ) × ( 0, h ) which is coupled via a nonlinear boundary condition with a second order semilinear ODE posed on ( − 1, 1 ) × 0 . The main result of the article is existence of the unique steady state for all ranges of parameters present in the system. Moreover we consider the problem of the dimension reduction. After introducing an appropriate scaling in the model we prove that, as h → 0, the stationary solution converges to the unique steady state of the one dimensional simplification of the model which was analysed in the first part of the series of papers. The main difficulty in obtaining appropriate estimates stems from the presence of a measure source term in the boundary condition.